Évangélisation, science et empire au tournant du siècle (fin du XVIIe-début du XVIIIe siècle). Le Florilegio medicinal (1713) du frère jésuite Juan de Esteyneffer : un vade-mecum de médecine pour les missions de la Nouvelle-Biscaye. - Amaia Cabranes (Centre de Recherches sur les Mondes Américains, 2017)
Juan de Esteyneffer was a missionary and travelling physician who belonged to the network of missions of the Society of Jesus in New Biscay between 1699 and 1715. He wrote the Florilegio medicinal as a tool for missionaries, whose practice of medicine among the indigenous population was considered to be an evangelization strategy. Thanks to his knowledge and his missionary experience in the field, Juan de Esteyneffer designed a particularly, comprehensive, balanced and flexible compendium which soon became an editorial success. The study of the book enables to examine the strategies followed by the Jesuits, and from a wider perspective, those implemented in frontier areas by the imperial administration at this pivotal time. A book of medicine, the Florilegio was devised as a tool of power to control men and territories ; further analysis of the book discloses how adaptation processes occurred, and even how the Americanization of actors and means arose.